2015
DOI: 10.1016/j.ijhm.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Management learning from air purifier tests in hotels: Experiment and action research

Abstract: a b s t r a c tRecently, indoor air quality (IAQ) has become an important issue as it affects people's comfort and health. To mitigate the problem, application of some innovative air filtering devices has been generally recognized as one of the effective ways. This study adopted an action research-dominated approach to test whether the indoor air quality in the tested hotel rooms meets the recognized standard, and measure the pollutant removal efficiency of three types of air purifiers. Focus group discussion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…For future studies, one American hotel brand in Japan places an air purifier in each guestroom, claiming that it removes up to 99.9 per cent of airborne contaminants (Dryfhout, 2016). As noted earlier, Chan et al (2015) demonstrated a maximum of 27.8 per cent decrease in PM 2.5 concentration in a vacant guestroom as a result of a 24-h air purifier treatment. It would be interesting to see if air purifiers minimize indoor PM exposure to guests and employees when the identified guestroom activities are performed.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…For future studies, one American hotel brand in Japan places an air purifier in each guestroom, claiming that it removes up to 99.9 per cent of airborne contaminants (Dryfhout, 2016). As noted earlier, Chan et al (2015) demonstrated a maximum of 27.8 per cent decrease in PM 2.5 concentration in a vacant guestroom as a result of a 24-h air purifier treatment. It would be interesting to see if air purifiers minimize indoor PM exposure to guests and employees when the identified guestroom activities are performed.…”
Section: Discussionsupporting
confidence: 67%
“…The other study did investigate PM 2.5 pollution in the guestrooms in China. Chan et al (2015) conducted a four-day field test to see if the IAQ in vacant rooms on a non-smoking floor meets the recognized standard at a hotel in South China where smoking is allowed on certain floors. They measured an average of PM 2.5 concentration for a period of 8 h in a pilot test.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Insights gained from experiments can further be enriched with complementary research methods, combining, for example, a laboratory and a field experiment; secondary data analysis and a laboratory experiment; or a qualitative study and an experiment. Examples in tourism include: Kim and Jang (2014) who complement their laboratory experiment with a field study, Walters et al (2019) who run a choice experiment embedded within a classic between experimental design, and Chan et al (2015) who offers evidence from a qualitative study and an experiment. The nature of participants and the degree of behavioural measures may differ across the empirical package.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental quality in general, and IAQ in particular, has been perceived as an element of concern even before the present crisis, in the hospitality sector [31], as well in sectors related to it (e.g., airport facilities management [32]), as IAQ is recognized as an element to enhance the health and comfort of travelers and, therefore, a selling point with high growing potential. Previous studies in the field focused mainly on PM monitoring [6,13,31,33,34], and for limited periods of time (e.g., hours, in the case proposed by Asadi et al [33], or days [34]).…”
Section: Introductionmentioning
confidence: 99%